Lithium (Li) geochemistry of oilfield brines: An example from petroliferous basins in southeastern Turkiye - Doner, Zeynep; Ünal, Alp; Ozdamar, Senel; Kumral, Mustafa; Sutcu, Naside Merve; Billor, Mehmet Zeki; Lee, Ming-Kuo; Zou, Haibo; Bahtiyar, Ismail; Eyeci, Huseyin; Temel, Riza Ozgur (Copernicus GmbH, 2026)
Lithium (Li) has become a critical and strategic metal owing to its distinctive physical and chemical properties and its wide range of applications, including batteries, ceramics, glass production, nuclear materials, and lubricating greases. Oilfield brines represent a significant alternative Li resource capable of meeting increasing global demand in the coming decades, and most petroliferous basins are known to contain Li-enriched formation waters. This study investigates the origin of Li in oilfield brines from actively producing fields operated by the Turkish Petroleum Company in southeastern Turkiye. Southeastern Anatolia, which hosts the main oil-producing fields of Turkiye, is located at the northern margin of the Arabian Plate and experienced Paleozoic epirogenic movements associated with the Caledonian and Hercynian orogenies. These tectonic events played a key role in shaping the regional structural framework, controlling basin architecture and long-term fluid pathways that governed the amount and origin of oilfield brines. The Ca, Na, and molar ratios of Cl/Br, Na/Cl, Ca/Mg and Ca/Sr in the brines indicate the influence of multiple diagenetic processes, including halite dissolution, dolomitization, albitization, and calcite or anhydrite cementation. The studied brines contain Li concentrations (up to 10 mg/L) and are characterized by relatively low B, Br, and Sr contents. The salinity of the brines within the sedimentary basins is primarily attributed to evaporation and/or evaporite dissolution. Minor contributions from halite dissolution are indicated by the moderate correlation between the molar Cl/Br and Na/Cl ratios. Furthermore, relatively strong relationships between Li concentration, salinity, and Cl/Br ratios support this interpretation. Trends observed in Ca/Mg and Ca/Sr molar ratios further suggest the occurrence of dolomitization and calcite recrystallization processes. Overall, these results indicate that further integrated studies are required to better constrain modes of occurrences of Li, highlighting the significance of oilfield brines in southeastern Turkiye.